A longitudinal study of selected impacts of the School District Finance and Quality Performance Accreditation (SDFQPA) Act on representative Kansas school districts, 2002-2011 - Jordan, Brian C. (Kansas State University, 2012)
Information gained from the present study should provide important policy insights into whether adjustments to the School District Finance and Quality Performance Accreditation (SDFQPA) Act funding formula have supported the original goal behind SDFQPA, which was to provide more equal funding to public elementary and secondary pupils in Kansas. The study assessed selected fiscal and pupil performance impacts following changes to the SDFQPA funding formula during the years 2002 - 2011. The information gained from the present study also can be compared with the insights gained from the DeBacker study of 2002 which analyzed SDFQPA funding formula impacts from 1992 - 2001. The result of extending and expanding the DeBacker study to new data in 2011 is significant. When considered jointly, information from the two studies should provide insight about selected school funding variables impacted by the SDFQPA funding formula over a twenty-year span. The population for the study included all 289 Kansas school districts in existence in 2011. The study sample, 112 school districts, was arranged into decile groups based on assessed property valuation in 2002. The design resulted in 28 school districts in four decile groups of Deciles 1, 5, 6, and 10. Decile 1 school districts were considered poor, Deciles 5 and 6 were considered average wealth, and Decile 10 school districts were considered wealthy. The study was conducted in two phases. The first phase consisted of an extensive data review based on the critical element of local fiscal capacity to support schools across two book-end years 2002 and 2011. The following represent the fiscal and student performance variables analyzed in the first phase: enrollment, general fund amounts per pupil, supplemental general fund amounts per pupil, capital outlay fund amounts per pupil, bond and interest fund amounts per pupil, number of pupils per certified employee, and average teacher salaries. Other pupil performance variables examined included: graduation rates, dropout rates, and state reading and math assessment results. The second phase of the study attempted to expand on researcher observations made during the first phase through the use of surveys and telephone interviews. Surveys were mailed to the 112 school districts in the study sample to gather contextual information about the specific variables and also to gather information not available from the data. Survey information included the following: construction or remodeling of facilities, closing or combining of schools, and changes in secondary curricular offerings. Telephone interviews were also conducted with 5 randomly selected school districts from each of the four studied deciles to clarify the survey data and to gather school leaders’ perceptions about changes to the SDFQPA funding formula. Results of the study indicated that adjustments to SDFQPA from 2002-2011 did indeed increase the level of fiscal resources available to average wealth school districts at a greater rate than resource increases experienced by wealthy school districts. Pupil performance across all deciles improved, with the most dramatic improvements occurring within the average wealth school districts. The school districts within Decile 1 experienced the most improvements to facilities, and increases in curricular offerings when compared to other deciles. The results indicated that positive changes have occurred in the educational experience offered by Kansas school districts from 2002-2011. The positive changes were discovered with only cautious optimism, however, as more recent changes to SDFQPA could potentially undo the growth experienced by Kansas school districts from 2002 to 2011.
Keywords: Education Finance; Education Administration; Education Finance (0277)